2012
DOI: 10.4103/0253-7613.100378
|View full text |Cite
|
Sign up to set email alerts
|

Study of antiurolithiatic activity of Asparagus racemosus on albino rats

Abstract: Aims:The aim of this study was to investigate the effect of ethanolic extract of Asparagus racemosus on urolithiasis in rats.Materials and Methods:Thirty-six male Wistar albino rats were randomly divided into six groups (n = 6). Ethylene glycol (EG) 0.75% and ammonium chloride (AC) 2% in drinking water were fed to all groups (Groups II–VI) except normal control (Group I) rats for 10 days to induce urolithiasis. Group III–VI rats were treated with ethanolic extract of Asparagus racemosus at doses 200, 400, 800,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Although serum creatinine is not considered an ideal biomarker of glomerular filtration rate (GFR), it can be used to estimate overall renal function in the absence of more sensitive markers 23 . Some authors have reported a correlation between decreased renal function and urolithiasis due to urinary obstruction and damage of the renal parenchyma 24,25 . In this study,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serum creatinine is not considered an ideal biomarker of glomerular filtration rate (GFR), it can be used to estimate overall renal function in the absence of more sensitive markers 23 . Some authors have reported a correlation between decreased renal function and urolithiasis due to urinary obstruction and damage of the renal parenchyma 24,25 . In this study,…”
Section: Discussionmentioning
confidence: 99%
“…However, when the animals were followed for 28 days, there was no statistical difference in serum creatinine in the different groups. Considering that the prolonged period of exposure to different inducing agents could cause deterioration in the renal function 25 , normal levels of creatinine at M2 suggests that the initial statistical difference observed in M1 could be considered a biological variation.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Antiurolithiatic spectrum (reported): Roots against whewellite. [35] Asphodelus aestivus Brot. Dioscorides (De Materia Medica): Roots are diuretic [22] ; Aerial parts ---Turkey.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…Ethylene glycol induced urolithiasis model was used for the experiment [9][10] . The model was customized for 15 days of study.…”
Section: Anti-urolithiatic Studymentioning
confidence: 99%